2021
DOI: 10.3390/su13084402
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to the Operation Modes and Strategies for Integrated Hybrid Parabolic Trough and Photovoltaic Solar Systems

Abstract: Concentrated solar power (CSP) and photovoltaic (PV) solar systems can be hybridized, creating synergies: on one hand procuring dispatchability by storing thermal energy, and on the other hand generating electricity at a highly competitive prize. In this paper, we present an approach to the operation strategies and modes for integrated hybrid CSP + PV systems. We focus on parabolic trough (PT) solar plants, especially those operating in the south of Spain. Our study consists in the definition of suitable state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…The collector was found to became more evenly distributed in temperature when the main channel and subchannel diameter ratios increased, so that the channels with D/d = 4 could be 50% greater than those with D/d = 2. López-Álvarez et al [4] developed an operation-control algorithm for hybrid concentrated solar power (CSP) with solar PVs in the south of Spain and reported good retrofitting possibilities for the CSP plants in operation. Kim et al [5] showed that the building-integrated photovoltaic-thermal (BIPVT) system could produce 30 W more power than the BIPV system, and the maximum difference in temperature between BIPVT and BIPV was about 22 • C during the winter season.…”
Section: Introductionmentioning
confidence: 99%
“…The collector was found to became more evenly distributed in temperature when the main channel and subchannel diameter ratios increased, so that the channels with D/d = 4 could be 50% greater than those with D/d = 2. López-Álvarez et al [4] developed an operation-control algorithm for hybrid concentrated solar power (CSP) with solar PVs in the south of Spain and reported good retrofitting possibilities for the CSP plants in operation. Kim et al [5] showed that the building-integrated photovoltaic-thermal (BIPVT) system could produce 30 W more power than the BIPV system, and the maximum difference in temperature between BIPVT and BIPV was about 22 • C during the winter season.…”
Section: Introductionmentioning
confidence: 99%